Shepard's war : E. H. Shepard : the man who drew Winnie-the-Pooh - Shepard, Ernest H. (LOM Art, 2015)
Ernest Howard Shepard was born in London in 1879 into an artistic and literary family. He studied art from an early age and was successful in making a career out of it, particularly as a political cartoonist for Punch and a prolific book illustrator. Shepard is most widely known for his illustrations of the Winnie-the-Pooh series by A.A. Milne and The Wind in the Willows by Kenneth Grahame, and these drawings have become classics in their own right, iconic in the minds of children and adults everywhere. Shepard's War is an intimate, illustrated narrative of the First World War seen through the mainly unpublished work of E.H. Shepard, who served as a frontline officer from 1915 to the end of the war. With over a hundred pieces of original artwork, rendered in full-colour, ranging from caricatures of Shepard's fellow officers to sketches made during battle, technical drawings and commentary from Shepard's own wartime notebooks and diaries, this is a unique insight into the life of an incredibly talented yet humble man and a rare visual journey into the Great War.